Photocatalysis Unveiled: Fundamentals, Mechanisms, and Material Innovations - Babatunde Alabi (International Journal of Photochemistry and Photochemical Research, 2025)
The Industrial Revolution significantly enhanced living standards but also led to severe environmental degradation, making pollution a critical concern for both developed and developing nations. Photocatalysis, a light-driven chemical process, accelerates thermodynamically demanding reactions, such as photosynthesis, offering a promising alternative for deep solar energy storage. This method also minimizes chemical exposure and reduces environmental pollutants generated by industrial activities. A key advantage of photocatalysis is its ability to replace high-temperature pollution removal processes with more energy-efficient, low-temperature alternatives, thereby conserving fossil fuel resources.Various photocatalytic materials, including AgCl, P-doped g-C₃N₄, and Z-scheme photocatalysts coupled with Fe₃O₄/H₂O₂, have gained attention due to their multiple valence states and high catalytic efficiency. A critical focus of this review is the Z-scheme strategy, which enhances electron transport pathways by forming heterojunctions with optimal band alignments, thereby improving the photocatalytic activity of MnO₂. The article explores recent advancements in photocatalysis, MnO₂-based composite materials, and the Z-scheme charge carrier mechanism.Additionally, the electrical, photoelectric, and crystallographic properties of MnO₂ are examined, emphasizing the significance of the Z-scheme electron transfer process in enhancing photocatalytic performance. Various electron transport pathways in MnO₂-based composites are investigated using different characterization techniques to provide deeper insights into the Z-scheme mechanism. This review comprehensively discusses the fundamental principles, processes, and materials in photocatalysis, highlighting its potential for environmental sustainability and energy-efficient applications.
Keywords: Electron transport pathways; Heterojunctions; MnO₂-based composites; Z-scheme mechanism; photocatalysis